Wellness Tourism in India during Post COVID-19 Era: Opportunities and Challenges - Choudhary, Bushra; Qadir, Abdul (Turizam, 2022)
The highly infectious novel coronavirus has hit hard the various segments within the tourism industry and raises questions on their survival. While the COVID-19 had severely impacted the tourism industry globally at the same time it has developed the importance of maintaining health and wellness among people. India is a home of various ancient practices such as Ayurveda, Yoga, and other practices that come under AYUSH, therefore, both domestic and international tourists visit India to undertake medical and wellness tourism. This paper explores the opportunities and challenges of wellness tourism in India in the post-corona times and it further aims to provide a way to conduct future research. This paper is based on the secondary data which was accumulated through sources like newspaper articles, magazines, books, the internet, media reports. The finding of the study reveals that medical and wellness tourism is expected to rise and recuperate the Indian tourism sector in post-COVID-19. The study also identifies the potential of the Indian wellness tourism industry and government initiatives to develop this sector in the post-pandemic times.
Keywords: Health Tourism; Wellness tourism; post-COVID-19; Opportunities; Challenges